Phubbing, Komunikasi Interpersonal, dan Etika Komunikasi dalam Masyarakat - Constantin, Natasha; Setijadi, Naniek (UNIVERSITAS SARI MUTIARA INDONESIA, 2023)
Currently, technology is rapidly increasing advancing and developing. Communication technology, especially smartphones, has experienced rapid development with up-to-date technologies and features attached. Amidst the rapid development of technology and features attached to communication tools, the phubbing phenomenon has emerged which occurs at almost all levels of society. The emergence of this phenomenon become one of the developments of communication technology especially cell phones negative impacts, which results in the disruption of relationships between individuals due to too much focus on cell phones. This phenomenon has a bad impact on technological developments and hurts phubbers mental health. literature reviews or desk research. The aim is to provide a comprehensive knowledge of the phubbing phenomena, which is happening unintentionally in society, by drawing on prior research. This article’s purpose is to provide a comprehensive understanding of phubbing and its effects on communication and mental health in society. The goal is to raise awareness and propose preventive measures to mitigate any additional adverse consequences. The findings of this paper demonstrate that the phubbing phenomenon is a negative consequence resulting from the quick and substantial advancements in technology. In Indonesian society, the phenomenon of phubbing is not widely recognized. From the standpoint of communication ethics, this phenomenon is clearly the opposite of face-to-face communication norms and ethics, as it involves disregarding the individual with whom one is conversing. Ultimately, comprehensive community involvement and extensive study are essential to gain a deeper understanding and develop proactive strategies to address the rise of the phubbing phenomena.